IMPROVING STUDENT DISCIPLINE IN HIGHER EDUCATION INSTITUTIONS - Saidkhojaeva Barno; Ibragimova Ra'no Khamdamovna (Galaxy International Interdisciplinary Research Journal, 2023)
The increasing prevalence and severity of mental health difficulties in the population of university students is an important issue for universities and their wider communities. Little is still known about student perspectives on stressors in the university environment and what steps universities take to better support student mental well-being. Partially covered in this article